Γ-Valerolactone as an alternative biomass-derived medium for the Sonogashira reaction. Issue 2 (11th November 2014) - Strappaveccia, Giacomo; Luciani, Lorenzo; Bartollini, Elena; Marrocchi, Assunta; Pizzo, Ferdinando; Vaccaro, Luigi
Abstract : γ-Valerolactone (GVL) can be used as an efficient and practical alternative to the banned and commonly used dipolar aprotic solvents. Abstract : γ-Valerolactone (GVL) can be used as an efficient and practical alternative to the banned and commonly used dipolar aprotic solvents. In this contribution GVL has been used as a non-toxic, biodegradable, biomass-derived medium, for the definition of a simple and general protocol for the Sonogashira cross-coupling reaction. The chemical efficiency of GVL as a medium is excellent and the best results have been obtained using DABCO as the base allowing the isolation of products3a–q in 60–96% yields. These results represent an example which proves that biomass-derived safer solvents can be used efficiently in common transformations reaching higher greenness/sustainability as well as high chemical efficiency.